Analyzing Ideological Manipulation In Twitter Communication:A Critical Stylistic Analysis Of Imran Khan’s Tweets - Sarwar, Mamoona; Bhatti, Dr. Zafar Iqbal; Nasreen, Shabana (Migration Letters, 2024)
Social media is the most recent interest of political communication diplomatists. It has turned into a significant source of political information (Enli, 2017). Social media has been successfully adopted as a platform for marketing. Social media also get the attention of politicians. Many politicians are using this as an effective communication tool. Many researchers from several disciplines are looking into different topics. These days analysis of social websites like Twitter, Instagram, and Facebook is in trending. It is easy to examine the sentiments and viewpoints of social media users because the data is easily available on it (Alaghbary, 2022). Likewise, Twitter is a vital and emerging medium. It is used to bridge the people, broadcast information and news. Some people are using it for public awareness and to educate the people. Twitter is also increasingly used for election campaigns by politicians. It permits its clients to get standard updates about political occasions, associate with political personnel, respond to political news, and participate in political exercises. To analyse the language used by politicians on social media is quite in trend (Linz, et al., 2021). My study also focuses on the critical stylistic analysis of the language of a politician used on Twitter.